Analisis Insight Instagram sebagai Media Pemberdayaan Digital pada Komunitas Pertanian Perkotaan - Fadhil Ahla Firdaus; Nurlaela, Siti; Mastur, Mastur (Journal of Agribusiness Science and Rural Development, 2025)
The development of the era demands the optimization of the use of the Instagram platform as a strategic digital empowerment tool in supporting the effectiveness of information dissemination, increasing community participation, and strengthening the management of sustainable urban agriculture in the context of digital transformation. This study uses a qualitative descriptive approach, by collecting data and analyzing it in depth to describe the facts systematically, factually, and accurately. The qualitative approach allows researchers to understand the phenomena that occur based on experience and interpretation of data in the form of speech, writing, and behavior. Instagram insight analysis was carried out on data on impressions, reach, and content interactions recorded during the period from November 20, 2023 to April 28, 2025. The informant selection technique was also carried out purposively, involving six informants consisting of four key informants and two additional informants. The results of the study show that the Instagram account @great.andgreen experienced positive growth with a total of 1,335 followers, dominated by users aged 18–24 years. This encourages the use of a non-formal language style that is adjusted to the characteristics of a young audience. The total number of impressions obtained was 130,413 with the highest impressions coming from the promotional content "Holiday Farm". The content reach reached 18,991, with the highest reach on the educational video on maggot cultivation. The high reach shows great potential in expanding influence beyond the main followers. Content interaction also showed positive results reaching 2,215 interactions through the number of likes, saves, comments, and shares. Digital utilization includes elements such as brand story, brand mission, product samples, community development, memorable content and packaging, and differentiation.